Living off Trash in Latin America: debunking the Myths - Medina, Martin (2015)
As a child growing up in mexico, i often saw men, women, children and the elderly picking through other people’s trash, searching for reusable and recyclable items. Due to their daily contact with garbage, ragged appearance, and often low educational levels, scavengers were considered the poorest of the poorand the lowest of the low in Mexican society. Most Latin American societies have traditionally viewed their own scavengers similarly. Only the poorest and most desperate would be willing to handle trash and sometimes live next to garbage dumps, in order to survive. Scavengers can be found in most cities in the developing world. Yet they are largely ignored by researchers, policy makers and society in general. My experience researching scavengers over the past 15 years may serve to debunk some commonly held beliefs about this population and their activities.